The combined effects of alcohol and cannabis on driving: Impact on crash risk. (March 2015) - Dubois, Sacha; Mullen, Nadia; Weaver, Bruce; Bédard, Michel
Highlights: We examined combined THC/alcohol crash culpability in fatal car crashes. Since 1991, a five-fold increase in combined THC/alcohol prevalence has occurred. Each 0.01 BAC unit increased the culpability odds (COs) by approximately 9–11%. Drivers who were positive for THC alone had 16% increased COs. Combined THC/alcohol COs were greater than COs for alcohol or THC alone. Abstract: Background/objectives: Driving under the influence of alcohol or cannabis alone is associated with increased crash risk. This study explores the combined influence of low levels of alcohol (BAC ≤ 0.08) and cannabis on crash risk. Materials and methods: Drivers aged 20 years or older who had been tested for both drugs and alcohol after involvement in a fatal crash in the United States (1991–2008) were examined using a case–control design. Cases were drivers with at least one potentially unsafe driving action (UDA) recorded in relation to the crash (e.g., weaving); controls had none recorded. We examined the prevalence of driving under the influence of alcohol, cannabis, and both agents, for drivers involved in a fatal crash. Adjusted odds ratios of committing an UDA for alcohol alone, THC alone, and their combined effect were computed via logistic regression and adjusted for a number of potential confounders. Results: Over the past two decades, the prevalence of THC and alcohol in car drivers involved in a fatal crash has increased approximately five-fold from below 2% in 1991 to above 10% in 2008. Each 0.01 BAC unit increased the odds of an UDA by approximately 9–11%. Drivers who were positive for THC alone had 16% increased odds of an UDA. When alcohol and THC were combined the odds of an UDA increased by approximately 8-10% for each 0.01 BAC unit increase over alcohol or THC alone. Conclusion: Drivers positive for both agents had greater odds of making an error than drivers positive for either alcohol or cannabis only. Further research is needed to better examine the interaction between cannabis concentration levels, alcohol, and driving. This research would support enforcement agencies and public health educators by highlighting the combined effect of cannabis at low BAC levels.